ODK Viewer: A tool to visualise ODK (version 1) data on Android devices - Quirós, Carlos F. (International Livestock Research Institute, 2014)
ODK Viewer is a tool that complements ODK by displaying on-device data in tabular form and allows easier reviewing and editing of data before submission to the server.